It occurs to me that I am America : new stories and art - Santlofer, Jonathan, 1946-; Nguyen, Viet Thanh, 1971- (New York : Touchstone, 2018)
"In time for the one-year anniversary of the Trump Inauguration and the Women's March, this provocative, unprecedented anthology features original short stories from thirty bestselling and award-winning authors--including Alice Walker, Richard Russo, Walter Mosley, Joyce Carol Oates, Alice Hoffman, Neil Gaiman, Michael Cunningham, Mary Higgins Clark, and Lee Child--with an introduction by Pulitzer Prize-winning author Viet Thanh Nguyen"--
Keywords: Short stories, American; American fiction -- 21st century; FICTION / Anthologies (multiple authors).; FICTION / Political; LITERARY COLLECTIONS / American / General